A SPATIO -TEMPORAL CHANGES OF RURAL AND URBAN POPULATION IN BAGALKOT DISTRICT: A GEOGRAPHICAL STUDY (International Journal of Food and Nutritional Sciences, 2022)
The distribution of a population between urban and rural areas is one of the most crucial factors. The easiest method to learn more about this is through the census. It is important to distinguish between rural and urban populations since they have quite different economies, lifestyles, social statuses, and other characteristics. This study's main goal was to monitor changes in the proportion of people living in rural and urban areas in the Bagalkot region. This study also analyses the population changes between rural and urban areas between2001 and 2011. Further, the research article project's light on the shift in the ratio of urban to rural population growth over the ten years i.e. 2001 and 2011. the present study growth rate of the rural population was negative in the district was about -2.67 percent during 2001-2011. And the growth rate of the Urban population was positive in the district was about 2.67 percentfrom 2001-2011.